PERANAN DOMAIN PENAFSIRAN DALAM MENENTUKAN JENIS KUANTOR - Septilia Arfida (IIB Darmajaya, 2011)
Logic holds an important role in Computer Academic is used as a basic for programming language, Data Base, Artificial Intelligent, Software Engineering, and etc. It can be concluded that if we want to learn about computer, so it will be connected to logic. Logic is one of knowledge which can’t stand alone. It can be used to evaluate and organize the structure of arguments and statements which are collected from the study of the argument and formal system effect to daily human language. Quantifier is a sentence that conatains that quantity of expression involved eg existing objects, all, some, not all, and others. Quantifier consists of two forms Universal Quantifier and Existensial Quantifier. Universal Quantifier has the word - a word that implies a general and comprehensive while Existensial Quantifier have words – words that contain some sprecial meaning. Domain of quantifier interpretation is very important to determine the type of quantifier which would be used and affect its symbol. Key Word: Quantity Object, Universal Quantifier and Existensial Quantifier, and Domain